2020
DOI: 10.1111/mec.15664
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification induces distinct transcriptomic responses across life history stages of the sea urchin Heliocidaris erythrogramma

Abstract: Increased ocean uptake of carbon dioxide (CO 2) due to rising anthropogenic emissions is causing rapid alterations to the biological, chemical, and physical composition of the marine environment (Gattuso et al., 2015; IPCC, 2014). These changes have resulted in a multidimensional set of stressors for marine life as the ocean becomes more hypercapnic (increasing pCO 2), more acidic, and less saturated in calcium carbonate minerals (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 135 publications
0
13
0
Order By: Relevance
“…For example, gene expression studies of early developmental stages in coral identified a number of genes affected by OA (Moya et al, 2012;Rivest et al, 2018). Studies on sea urchins also revealed the overall molecular responses of sea urchin larvae exposed to CO 2 (Todgham and Hofmann, 2009;Devens et al, 2020). OA is known to interfere with several key physiological process in marine organisms, transcriptomics has proven to be effective method to elucidate the molecular level response and when coupled with phenotypic data confers a better understanding of whole organismal response (Davies et al, 2016;Melzner et al, 2020;Strader et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, gene expression studies of early developmental stages in coral identified a number of genes affected by OA (Moya et al, 2012;Rivest et al, 2018). Studies on sea urchins also revealed the overall molecular responses of sea urchin larvae exposed to CO 2 (Todgham and Hofmann, 2009;Devens et al, 2020). OA is known to interfere with several key physiological process in marine organisms, transcriptomics has proven to be effective method to elucidate the molecular level response and when coupled with phenotypic data confers a better understanding of whole organismal response (Davies et al, 2016;Melzner et al, 2020;Strader et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, this reduction could potentially be an issue for differential gene expression studies where gene variants (i.e., isoforms) are removed from the samples via the reduction of transcripts. Nevertheless, performing a reduction step before a gene expression analysis is a common practice (DeLeo & Bracken‐Grissom, 2020; Devens et al, 2020; Guo et al, 2017; Kashyap et al, 2020; Perez et al, 2021). Therefore, the nonredundant transcriptome generated by TransPi could be utilized for gene expression studies (Deshpande et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, thousands of genes were exclusively responsive in a single life stage with only ∼20% DEGs consistently responding to salinity stress in this earlier study, reinforcing a largely stage-specific stress response (Aguilar et al, 2019b). Although sparse, there is also evidence for development modulating the stress response in plants (Garg et al, 2016; Liu et al, 2021) and other invertebrates (Devens et al, 2020; Schneweis et al, 2017), suggesting complex life cycles can decouple the molecular response to stress. The lack of consistency in the stress response across life stages has major implications for the evolutionary trajectory of these corals.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of expression response to stress in Acroporid corals, Dixon et al (2020) found life stage to be the major factor differentiating transcriptional variation, but most studies were limited to a single life stage, precluding any formal investigation of life-stage differences. However, developmental stage has been found to modulate the transcriptional response to stress in other systems, including water and salinity stress in plants (Garg et al, 2016; Liu et al, 2021), viral infection in insects (Schneweis et al, 2017), and pH stress in sea urchins (Devens et al, 2020). It is therefore necessary to explore how functional variation is regulated across different developmental stages to inform understanding of coral adaptive capacity.…”
Section: Introductionmentioning
confidence: 99%